1986
DOI: 10.1080/00480169.1986.35278
|View full text |Cite
|
Sign up to set email alerts
|

Viruses associated with respiratory disease of horses in New Zealand: an update

Abstract: Viruses causing or associated with respiratory disease in horses worldwide are reviewed. Results are presented from a serological survey of 121 New Zealand foals and horses that had been affected by respiratory disease, determining the prevalence of antibodies in this country to the major viruses associated with similar disease overseas. To date there is no evidence of equine influenza virus in New Zealand. Both equine herpesvirus type 1 and 2 have been frequently isolated and show high serological prevalences… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
9
0
1

Year Published

1988
1988
2008
2008

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(10 citation statements)
references
References 23 publications
0
9
0
1
Order By: Relevance
“…Purewal et al [34], Welch et al [45], Fortier et al [21], Jolly et al [28] and Nordengrahn et al [31] have linked EHV-2 with Streptococcus zooepidemicus, Rhodococcus equi, and S. equi. In our study, we could not establish a link between gammaherpesvirus infection and bacterial colonization as all swabs were transported to the laboratory in virus transport medium containing antibiotics and therefore unsuitable for bacteriology testing.…”
Section: Discussionmentioning
confidence: 99%
“…Purewal et al [34], Welch et al [45], Fortier et al [21], Jolly et al [28] and Nordengrahn et al [31] have linked EHV-2 with Streptococcus zooepidemicus, Rhodococcus equi, and S. equi. In our study, we could not establish a link between gammaherpesvirus infection and bacterial colonization as all swabs were transported to the laboratory in virus transport medium containing antibiotics and therefore unsuitable for bacteriology testing.…”
Section: Discussionmentioning
confidence: 99%
“…4,9,19,20,28,[39][40][41] However, infection with EHV2 appears to be widespread, and several studies have also found EHV2 in the respiratory tract and peripheral blood leukocytes of horses without clinical disease, with isolation and/ or PCR detection rates ranging from 31 to 89%. 4,19,33,35,39 Following experimental inoculation of EHV2 into both juvenile and adult horses, chronic pharyngitis was observed in the young horses while the adult horses remained clinically normal. 3 As with other gammaherpesviruses, latency in lymphocytes has been demonstrated for EHV2.…”
Section: Discussionmentioning
confidence: 99%
“…Previously, these viruses had been thought to be similar to other known cytomegaloviruses based on their biological properties (Roizman et al, 1992). However, the precise role of any of the current isolates of EHV-2 in relation to disease production in the horse is unknown and the viruses have been isolated from clinically normal horses as well as those showing clinical signs including upper respiratory tract disease, pneumonia, enlarged lymph nodes, conjunctivitis or general malaise (Studdert, 1971 ;Blakeslee et al, 1975 ;Sugiura et al, 1983 ;Jolly et al, 1986 ;Browning & Studdert, 1988).…”
Section: Introductionmentioning
confidence: 99%